Youngest Child Having Continuous Ambulatory Peritoneal Dialysis in Bangladesh : A Case Report - Hasan, A N M Saiful; Khan, Anwar Hossain; Maruf-Ul-Quader, Mohammed; Ul Alam, A B M Mahbub; Begum, Saukat Ara; Banik, Shukhamoy Kangsha; Hossain, Md Delwar; Begum, Rokeya (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
A 7 months old girl of a non-consanguineous parents admitted in the Department of Pediatric Nephrology, National Institute of Kidney Diseases and Urology (NIKDU), Sher-E-Bangla Nagar, Dhaka, who was diagnosed ultimately as a case of Chronic Kidney Disease (CKD) stage V. She had no family history of renal disease. Initially she was treated with Intermittent Peritoneal Dialysis (IPD). Later she was put on Continuous Ambulatory Peritoneal Dialysis (CAPD). With CAPD her serum creatinine gradually decreased and her general wellbeing becomes stable. She was the youngest child who had CAPD in Bangladesh. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21040